“It All Starts with Us”: Exploring teachers’ efforts to increase Adult SEL in practice - Addison M. Duane; Quinn Hafen; Pamela McVeagh-Lally; Valerie B. Shapiro (Social and Emotional Learning: Research, Practice, and Policy)
In this paper, we analyze presentations made by 212 teachers who were tasked with implementing adult social and emotional learning (SEL) practices in their local context and sharing about their efforts. We draw our sample from the University of California, Berkeley’s SEL Foundations course; an online graduate course for in-service educators. Course participants completed a final assignment over a three-week period, implementing one or more Adult SEL practices, and reflecting on implementation set-backs and successes. We generated five themes depicting the landscape of Adult SEL among these educators: (1) relationship building (e.g., attending social events, seeking out peer support); (2) lifestyle changes (e.g., sleep hygiene, movement); (3) self-reflection (e.g., journaling); (4) mindfulness (e.g., meditation, mindful awareness); and (5) boundary setting (e.g., leaving at contract time, limiting phone usage). We also explore these teachers’ reflections on their practice (e.g., successes and challenges) to facilitate a more enhanced understanding of the work of implementing Adult SEL. This systematic inquiry of Adult SEL practice illustrates the choices teachers make when asked to do a project to improve their Adult SEL. Findings offer valuable insights into what teachers today may want—and need—from their schools, districts, and the field of SEL more broadly.